2013
DOI: 10.2147/ijn.s44479
|View full text |Cite
|
Sign up to set email alerts
|

Computational study on the interactions and orientation of monoclonal human immunoglobulin G on a polystyrene surface

Abstract: Abstract:Having a theoretical understanding of the orientation of immunoglobulin on an immobilized solid surface is important in biomedical pathogen-detecting systems and cellular analysis. Despite the stable adsorption of immunoglobulin on a polystyrene (PS) surface that has been applied in many kinds of immunoassays, there are many uncertainties in antibodybased clinical and biological experimental methods. To understand the binding mechanism and physicochemical interactions between immunoglobulin and the PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 50 publications
2
10
0
Order By: Relevance
“…As the methyl protons of the ECL-II residues Val10 and Ile13 are located above the aromatic ring of DynA17 residue Trp14, they should interact in a CH/π manner. Similar interactions have been described for many biological systems [261]. Solidstate NMR experiments revealed that ECL-II also exhibits an α-helical structure in the region between Val10 and Ala15.…”
Section: Figure 18supporting
confidence: 76%
“…As the methyl protons of the ECL-II residues Val10 and Ile13 are located above the aromatic ring of DynA17 residue Trp14, they should interact in a CH/π manner. Similar interactions have been described for many biological systems [261]. Solidstate NMR experiments revealed that ECL-II also exhibits an α-helical structure in the region between Val10 and Ala15.…”
Section: Figure 18supporting
confidence: 76%
“…27 In another research, Javkhlantugs and coworkers postulated that positively charged guanidine group of arginine would closely contact with the benzene ring of the PS, which would indicate the existence of cation-p interaction between them. 28 Quadrupolar characteristic of the aromatic system enables polystyrene to offer adsorption for cations in water. A quadrupolar is originated from the uneven distribution of p-electron above and below the face of an aromatic system (e.g., benzene ring).…”
Section: Introductionmentioning
confidence: 99%
“…21 Additionally, it was easier to immobilize the antibodies on the PS nanosphere surface than on the silica fiber surface. 29 (The delocalized π-electrons in the aromatic ring of PS surface 34 interacted with the electrons of aldehyde groups of glutaraldehyde, making the glutaraldehyde distribute on its surface evenly and closely. This led to an easier and more uniform binding of antibody on the PS surface.…”
Section: ■ Results and Discussionmentioning
confidence: 99%